2021
DOI: 10.1371/journal.pntd.0008267
|View full text |Cite
|
Sign up to set email alerts
|

Tsetse blood-meal sources, endosymbionts and trypanosome-associations in the Maasai Mara National Reserve, a wildlife-human-livestock interface

Abstract: African trypanosomiasis (AT) is a neglected disease of both humans and animals caused by Trypanosoma parasites, which are transmitted by obligate hematophagous tsetse flies (Glossina spp.). Knowledge on tsetse fly vertebrate hosts and the influence of tsetse endosymbionts on trypanosome presence, especially in wildlife-human-livestock interfaces, is limited. We identified tsetse species, their blood-meal sources, and correlations between endosymbionts and trypanosome presence in tsetse flies from the trypanoso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 79 publications
3
16
2
Order By: Relevance
“…There is also evidence that some Sodalis genotypes can favour the establishment of trypanosme infections in tsetse flies by inhibiting the trypanocidal activity of the Glossina midgut lectin (e.g. [ 269 , 274 , 296 298 ]), although this varies with species, location and study [ 271 , 276 ].…”
Section: Paratransgenesis In Different Groups Of Vectorsmentioning
confidence: 99%
“…There is also evidence that some Sodalis genotypes can favour the establishment of trypanosme infections in tsetse flies by inhibiting the trypanocidal activity of the Glossina midgut lectin (e.g. [ 269 , 274 , 296 298 ]), although this varies with species, location and study [ 271 , 276 ].…”
Section: Paratransgenesis In Different Groups Of Vectorsmentioning
confidence: 99%
“…The distance between traps at each site was 200–500 m. Trapped flies were collected at 17.00 pm each day, which has been found to be the highest interaction period between hosts and tsetse flies 26 . The number of flies we aimed to capture was aound 100 samples based on prevous studies which have used 100–200 flies 35 , 40 . Whole flies were preserved in 95% ethanol and storage at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, humans, cattle, dogs, bush pigs, African buffaloes, warthogs, greater kudus, rats, and bats were confirmed as the blood-meal sources of tsetse flies in Zambia, using 12S ribosomal RNA (rRNA) gene deep sequencing [ 7 ]. Analysis of tsetse flies using vertebrate cytochrome c oxidase I (COX1) and cytochrome b gene polymerase chain reaction (PCR) revealed that humans are the most common vertebrate hosts [ 8 ]. This also indicated that other wild species, such as hippopotamuses, African buffaloes, African savannah elephants, and giraffes, may be involved in trypanosomiasis transmission.…”
Section: Introductionmentioning
confidence: 99%